Analysis Of Effleurage Massage And Mozart Classic Music Therapy On Primary Dysmenorhore In Adolescent Girls At Islamic Boarding School Kararan Trenggalek District - Nur Yeny Hidajaturrokhmah; Erni Arisa Putri; Retno Palupi Yoni Siwi; Teti Ripursari (Journal of Health Science Community, 2025)
Dymenorrhea is lower abdominal pain that occurs before menstruation or during menstruation. Dysmenorrhea can make women unable to carry out daily activities such as studying, working and other daily activities and requires them to sleep. The aim of this research was to determine the analysis of effleurage massage therapy and Mozart classical music on primary dysmenorrhea in young women at the Trenggalek Islamic boarding school. The design of this research is quantitative with a pre-experimental design approach pretest-posttest one group. The independent variables of this research are effleurage massage therapy and Mozart classical music therapy, while the dependent variable is Primary Dysmenorrhea. The instrument used was the Numerical Rating Scale (NRS) for 35 respondents taken using a purposive sampling technique. The results of the pain level of respondents before being given therapy were that the majority experienced primary dysmenorrhea in the moderate pain category, namely on a scale of 4-6, 19 respondents (54%). After being given therapy, the majority of respondents experienced primary dysmenorrhea in the mild pain category on a scale of 1-3, 27 respondents (77%). The results of the study using the Wilcoxon test with a value of α = 0.05, it was found significantly 0,000, because the significance value was <0.05 which meant there was an effect of giving effleurage massage therapy and classical music Mozart on the decline in primary dysmenorrhea in the women's teenager in Islamic boarding schools by Trenggalek. Effleurage massage therapy can warm muscles and improve blood circulation, while Mozart classical music therapy can stimulate endorphin hormones which, if both therapies are carried out, can reduce pain.